2012
DOI: 10.1080/01635581.2012.718034
|View full text |Cite
|
Sign up to set email alerts
|

Serum Albumin Is Superior to Prealbumin for Predicting Short-Term Recurrence in Patients with Operable Colorectal Cancer

Abstract: The relationship between preoperative prealbumin and cancer survival has not been fully elucidated. The purpose of this study was to examine the relationship between preoperative nutritional conditions, including prealbumin and albumin concentrations, and the risk of recurrence in cases with operable colorectal carcinoma. One hundred fifty-eight patients who underwent elective colorectal resection were analyzed in this study. Of the eligible cases, 56 (35.4%) had decreased serum prealbumin and 15 (9.5%) had de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
42
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(51 citation statements)
references
References 30 publications
3
42
0
Order By: Relevance
“…However, in multivariate analysis, the prognostic significance of prealbumin, total protein levels and total lymphocyte counts was markedly reduced by serum albumin levels. Consistent with our results, previous studies reported that serum albumin levels carried a greater prognostic value than other nutritional indicators in patients with various malignancies [19,20]. In our opinion, this is not because serum albumin is a stronger indicator of nutritional status, but rather because it is involved in specific pathophysiological processes such as inflammatory responses.…”
Section: Discussionsupporting
confidence: 92%
“…However, in multivariate analysis, the prognostic significance of prealbumin, total protein levels and total lymphocyte counts was markedly reduced by serum albumin levels. Consistent with our results, previous studies reported that serum albumin levels carried a greater prognostic value than other nutritional indicators in patients with various malignancies [19,20]. In our opinion, this is not because serum albumin is a stronger indicator of nutritional status, but rather because it is involved in specific pathophysiological processes such as inflammatory responses.…”
Section: Discussionsupporting
confidence: 92%
“…A long term chronic inflammation could lead to vascular endothelial damage and increase vascular permeability, which could increase the level of ALB in interstitial fluid and result in decreasing of serum ALB. Previous studies had confirmed that a low level of ALB was associated with poor prognosis in a variety of malignant tumors, including GC [29], colorectal cancer [30], lung cancer [31], and breast cancer [32]. GLB was produced by immune organs and reflected the immune state [33], which contained a lot of acute reactive proteins such as α 1 -antitrypsin, α 2 -macroglobulin, and haptoglobin.…”
Section: Discussionmentioning
confidence: 99%
“…17 Interestingly, several studies demonstrated that serum albumin and globulin can be used as biomarkers for recurrence and prognosis in many types of cancer including lung cancer. 11,18,19 High level of albumin or low globulin level is associated with better survival. 2022 However, as a biochemical index, the testing of albumin or globulin alone can be influenced by many factors, which may limit their stability and application in clinic.…”
Section: Introductionmentioning
confidence: 99%